Onomatope pada Pamflet Digital Produk Komersial Makanan dan Minuman Berbahasa Jepang: Kajian Struktur - Irsan, Muhammad; Yohana Risagarniwa, Yuyu; Krisnawati, Ekaning (Humanis; Vol 28 No 4 (2024)DO - 10.24843/JH.2024.v28.i04.p10, 2024)
This research is a structural study that focuses on describing the syntactic categories and the types of Japanese onomatopoeia that taken from advertising pamphlets of commercial food and beverage products. The data analysis method that applied in this research is the intralingual pairing method. Some of the theories that used are the theory of syntactic categories from Ikuhiro and Lawrence (1998) as well as from Kaori (2006), the theory of onomatopoeia types from Kaori (2006) and the theory of sentence analysis through phrase structure trees from Tsujimura (1996). From the analysis that have done, it was found about 78 data, including 33 different onomatopoeias that appearing in 68 sentences on 48 digital pamphlets of commercial products from various brands. Based on syntactic categories, Japanese onomatopoeia can be categorized as verb, adjective, noun and adverb with particles and affixes as the marker that are quite diverse. Based on the type, Japanese onomatopoeia in digital pamphlets can be classified as giongo, giseigo, gitaigo, giyougo and also gijougo, with gitaigo is the most dominant type of onomatopoeia that used in digital pamphlets of food and beverages.